solve this differential equation

y(x+y^3)dx=x(y^3-x)dy.

Note by Sriram Raghavan
4 years, 6 months ago

No vote yet
2 votes

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

For the differential equation \[ \frac{dy}{dx} \; = \; \frac{y(x+y^3)}{x(y^3-x)} \] try the substitution \(y \,=\, x^{\frac13}u\), so that \[ \begin{array}{rcl}\displaystyle x^{\frac13}\frac{du}{dx} + \tfrac13x^{-\frac23}u & = & \displaystyle\frac{x^{\frac13}u(x + xu^3)}{x(xu^3-x)} \; = \; x^{-\frac23}\frac{u(u^3+1)}{u^3-1} \\ xu' + \tfrac13u & = & \displaystyle\frac{u(u^3+1)}{u^3-1} \\ xu' & = & \displaystyle\frac{2u(u^3+2)}{3(u^3-1)} \\ \displaystyle\int \Big(\frac{3u^2}{u^3+2} - \frac{1}{u}\Big)\,du \; = \; \int \frac{2(u^3-1)}{u(u^3+2)}\,du & = & \displaystyle\int \frac{4}{3x}\,dx \; = \; \tfrac43\ln x + c \\ \displaystyle \ln \Big(\frac{u^3+2}{u}\Big) & = & \tfrac43\ln x + c \\ [2ex] \displaystyle \frac{u^3+2}{u} & = & Ax^{\frac43} \\ u^3 + 2 & = & Aux^{\frac43} \\ xu^3 + 2x & = & Aux^{\frac73} \\ y^3 + 2x & = & Ax^2y \end{array} \]

Mark Hennings - 4 years, 6 months ago

Log in to reply

thanku sir

Sriram Raghavan - 4 years, 5 months ago

Log in to reply

I think the answer is x=(-y^3)

Shiva Raj - 4 years, 6 months ago

Log in to reply

i think tis is nt the answer ,,,the answer is given in the book..bt no steps..@shiva raj

Sriram Raghavan - 4 years, 6 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...